Pleiotropic effects of statins in sepsis - Giusto, Silvana Menegoto Nogueira Di; Queiroz, Kelly Cristina Batista de Souto; Raimundo, Rodrigo Daminello; Abreu, Luiz Carlos de; Sato, Mônica Akemi (ABCS Health Sciences, 2014)
The objective of this study was to review the effects of statin therapy in patients with signs of sepsis. A bibliographic search of articles published between 2009-2013 was performed in the MEDLINE/PubMed, SciELO and LILACS databases. Randomized controlled trials and observational clinical cohort studies were included. The results show that several clinical and observational studies have investigated the effect of statin in infection and sepsis, both pre-hospital continuous use (with or without interruption during hospitalization) or starting immediately post-hospitalization. Some studies describe positive and beneficial effects of statin therapy in the context of sepsis, including improvement on inflammatory parameters and mortality rates. However, these results do not hold on when statistic methods, which take into account different variables such as age, sex, comorbidities and severity disease, are applied. To date, no study has demonstrated strong and significant evidence regarding the reduction of morbidity and mortality in sepsis associated with the use of statin. This indicates that beneficial and protective effects have not been fully defined yet. More researches are required to confirm the results found so far.